The diagnosis of scabies by non-expert examiners: A study of diagnostic accuracy. - Millicent H Osti; Oliver Sokana; Christina Gorae; Margot J Whitfeld; Andrew C Steer; Daniel Engelman (Public Library of Science (PLoS), 2019)
Background Although scabies is estimated to be one of the most common skin conditions globally, prevalence data is not available in most settings. Disease mapping is required to develop and monitor successful control programs. Non-expert health workers are likely to play an important role in scabies mapping activities in endemic settings. Methodology Four non-expert health workers were trained in the diagnosis of scabies and impetigo. The health worker diagnosis was compared to a reference consensus diagnosis of two doctors experienced in diagnosis. The study was conducted in a primary school in Gizo, Solomon Islands, in August 2018. The six examiners consecutively assessed school students, blinded to each other's findings. Training and diagnostic procedures followed criteria for scabies diagnosis established by the International Alliance for the Control of Scabies in 2018. Principal findings Amongst the 171 students who underwent clinical assessment the prevalence of scabies and impetigo according to the reference standard was 55% and 45% respectively. Sensitivity of the non-expert health workers' diagnosis compared to the reference standard was 55.3% for scabies (95% confidence interval [CI], 50.1-60.4) with a specificity of 89.9% (95% CI 86-93.1) and 52.6% for impetigo (95% CI 46.9-58.3) with a specificity 97.8% (95% CI 95.7-99). Sensitivity for moderate to severe scabies was 93.5% (95% CI 86.3-97.6) with a specificity of 74% (95% CI 70.2-77.5). Conclusions Following brief training, the diagnostic accuracy of non-expert health workers for scabies and impetigo was promising, especially for moderate to severe disease. Modifications to training and processes are recommended to further improve accuracy. The diagnosis by non-expert health workers may be acceptable for scabies and impetigo mapping in endemic areas.